Political institutions, voter turnout, and policy outcomes - NARCISO, GAIA (My University, 2012)
This paper tests whether constitutions directly affect economic outcomes. By introducing citizens? political participation as the driving force connecting institutions to policy outcomes, we empirically show that voter turnout is the channel through which forms of government affect economic policies. We provide evidence of the existence of two relationships. First, presidential regimes appear to be associated with lower voter participation in national elections. Second, higher voter participation induces an increase in government expenditure, total revenues, welfare state spending, and budget deficit. We conclude that forms of government affect policy outcomes only through voter turnout.
PUBLISHED
Keywords: Politics; Electoral rule; voter participation; policy outcomes; International Development; International Integration